Women food producers in Barbados: national summary - Cummins, Dianne (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This document synthesizes national research results obtained over nearly a year during 1993-1994 and sets out the principal findings in the four research areas of the program, which were: analysis of the contributions of women to food production on small agricultural units and to the agricultural sector as a whole; Analysis of agricultural sector policies and programas and their effects on rural women; Evaluation of the technology utilized on small agricultural production units and the participation of women in these technological processes; A study of the roles of women in the processing and marketing of food products.